Pengaruh Komunikasi Nonverbal dalam Mewujudkan Komunikasi yang Efektif antara Agen dan Konsumen PT. Axa Financial Indonesia cabang Medan - Ara Auza (Mahesa Research Center, 2019)
This study entitled The Effect of Nonverbal Communication in realizing Effective Communication between Agents and consumers of PT. Axa Financial Indonesia, Medan branch. This study aims to determine the process of Nonverbal Communication carried out by Insurance Agents of PT. Axa Financial Indonesia Medan branch; to find out the role of nonverbal communication in realizing Effective Communication between Agents and Consumers PT. Axa Financial Indonesia Medan branch; and to find out forms of nonverbal communication by insurance agents PT. Axa Financial Indonesia can realize effective communication with consumers. The theory used in this study is the theory of interpersonal communication, non-verbal communication and effective communication. The research methodology is intended to describe how researchers describe the procedures for collecting data needed, as well as analyzing data. The method in this study is a case study method. The informants in this study were 5 informants consisting of 2 (two) insurance agents and 3 (consumers) insurance PT. AXA Financial Indonesia Medan Branch. Research results Nonverbal communication that is often used by agents is physical appearance. The neat and attractive physical appearance was noticed by agents. The dominant factor when making a presentation is the clear tone of voice and movement of the limbs / kinesik such as the hands and eyes.